CRYPTOSPORIDIOSIS IN CALVES WITH CHRONIC NON-RESPONSIVE DIARRHOEA - S.A.RIDHA, G. (The Iraqi Journal of Veterinary Medicine, 2022)
This research work was conducted to study the role of cryptosporidial infection in calves with chronic non-responsive diarrhoea (1-4 weeks old). The study shows that cryptoridium was common infections agent causing diarrhoea in calves during the first month of calf life. the prevalence of cryptosporidiosis in calves with chronic diarrhoea was 51.5%, using the method of safranin methylene blue staining of faecal smears from diarrhoeic calves. The infection rate was higher in calves of group A (closed breeding system) than those of calves in group B (open breeding system), as the study reveals the rate 65.6% and 42.3% respectively. The study also shows that infection was higher in calves of two weeks old (36.3%) than other age groups. cryptosporidium oocysts were also reported from few numbers of healthy non-diarrhoeic calves at rate of 8.1%.